Rheological and structural characterization of gels from whey protein hydrolysates/locust bean gum mixed systems - Rocha, Cristina M. R. (2009)
The gelling ability of whey proteins can be changed by limited hydrolysis and by the addition of other components such as polysaccharides. In this work the effect of the concentration of locust bean gum (LBG) on the heat-set gelation of aqueous whey protein hydrolysates (10% w/w) from pepsin and trypsin was assessed at pH 7.0. Whey protein concentrate (WPC) mild hydrolysis (up to 2.5% in the case of pepsin and 1.0% in the case of trypsin) ameliorates the gelling ability. The WPC synergism with LBG is affected by the protein hydrolysis. For a WPC concentration of 10% (w/w), no maximum value was found in the G′ dependence on LBG content in the case of the hydrolysates, unlike the intact WPC. However, for higher protein concentrations, the behaviour of gels from whey proteins or whey protein hydrolysates towards the presence of LBG becomes very similar. In this case, a small amount of LBG in the presence of salt leads to a big enhancement in the gel strength. Further increases in the LBG concentration led to a decrease in the gel strength.